Faktor-Faktor Yang Mempengaruhi Tingkat Kebangkrutan Pada Perbankan Syariah Periode 2013-2019 - Alyana, Oktia Vandriani; Munawar, Aang (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This research was conducted using banking financial statements for seven years, namely the period 2013 - 2019 from banks engaged in the financial sector. The analytical method used is financial ratio analysis By using financial ratio analysis, it can be seen that the LDR, NPL, CAR and NIM affect the level of bankruptcy in banks this can occur due to internal factors contained in a bank. Then the conclusion is that the LDR, NPL, CAR and NIM affect the bank's bankruptcy level. It can be seen in the financial statements of the results of the LDR, NPL, CAR and NIM produced by banks increasing and decreasing during the research period, this has caused the bankruptcy rate of banks to also increase and decrease. The banking industry tries to maintain its Z-score by maintaining the value of the LDR, NPL, CAR and NIM variables on the financial statements, although the factors produced are not too large and even below average, the factors have increased. The number of factors in the financial statements that are affected by the level of financial ratios and income that has decreased due to banks that have not been able to emphasize their income. Banks conduct policies well by maintaining health and profit growth in terms of financial statements. Keywords: LDR, NPL, CAR, NIM and Bank's Bankruptcy Rate